Assessment of the Relationship Between Bone Mineral Density and Disease Activity in Ankylosing Spondylitis Patients with Osteopenia - Hayal Güler; Nilgün Üstün; Veli Enes Bolaç; Abdullah Erman Yağız; Ayhan Mansuroğlu; Erhan Yengil; Ayşe Dicle Turhanoğlu (Galenos Yayinevi, 2013)
Summary Aim: Ankylosing Spondylitis (AS) is a chronic inflammatory disease. Spinal osteopenia is common in AS, probably due to immobility and local cytokine release. In this study, we evaluated the relationship between bone mineral density and disease activity in Ankylosing Spondylitis patients with osteopenia. Material and Methods: Sixty one AS patients (26F, 35M) were enrolled in this study. The disease duration, morning stiffness, Schober tests, Erythrocyte Sedimentation Rate (ESR) and C Reactive Protein (CRP) were analyzed and recorded. Disease activity was evaluated by Bath Ankylosing Spondylitis Disease Activity Index (BASDAI). Bone mineral density (BMD) was measured by using GE/LUNAR DPX PRO equipment. Results: The mean age and disease duration of the patients were 38.67±10.81 and 7.87±7.09 year. There was osteopenia in 34 (%55.7) patients. Spine and femur BMD values of this patients were 1.03±0.16 and 0.88±0.09. BMD measurements of 27 (%44.3) patient were found normally. Spine and femur BMD values of this patients were 1.20±0.11 and 1.11±0.15. There was not statistically significant difference between osteopenia and normal group in ESR, CRP, and BASDAI values (p>0.05). There was not correlation between BMD values and ESR, CRP, and BASDAI values in osteopenia group (p>0.05). Conclusion: In our study, we did not find relationship between bone mineral density and disease activity in AS patients with osteopenia. (Turkish Journal of Osteoporosis 2013;19: 28-31)